2006
DOI: 10.1111/j.1365-294x.2006.02997.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic structure at range edge: low diversity and high inbreeding in Southeast Asian mangrove (Avicennia marina) populations

Abstract: Understanding the genetic composition and mating systems of edge populations provides important insights into the environmental and demographic factors shaping species’ distribution ranges. We analysed samples of the mangrove Avicennia marina from Vietnam, northern Philippines and Australia, with microsatellite markers. We compared genetic diversity and structure in edge (Southeast Asia, and Southern Australia) and core (North and Eastern Australia) populations, and also compared our results with previously pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

22
100
4
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 185 publications
(133 citation statements)
references
References 72 publications
22
100
4
2
Order By: Relevance
“…Studies also show that genetic variations occurred along elevation gradients because topographical heterogeneity of plants habitat causes substantial changes in the environment (Byars et al 2009;Kumar et al 2014;Ohsawa and Ide 2008). It is also reported that at different altitudes strong isolation of populations may occur due to drastic differences in phenology between higher and lower altitudes and mountain barriers which restricts the gene flow between the populations causing complex and varied genetic variations (Arnaud-Haond et al 2006;Kumar et al 2014;Liu et al 2012). This is also supported by the present study where populations of the plain or sloppy belts of Garo hills exhibit low levels of genetic diversity and are distinct from the populations of the hilly terrain of Khasi, Jaintia and Ri Bhoi districts of Meghalaya, where diversity is higher.…”
Section: Discussionmentioning
confidence: 98%
“…Studies also show that genetic variations occurred along elevation gradients because topographical heterogeneity of plants habitat causes substantial changes in the environment (Byars et al 2009;Kumar et al 2014;Ohsawa and Ide 2008). It is also reported that at different altitudes strong isolation of populations may occur due to drastic differences in phenology between higher and lower altitudes and mountain barriers which restricts the gene flow between the populations causing complex and varied genetic variations (Arnaud-Haond et al 2006;Kumar et al 2014;Liu et al 2012). This is also supported by the present study where populations of the plain or sloppy belts of Garo hills exhibit low levels of genetic diversity and are distinct from the populations of the hilly terrain of Khasi, Jaintia and Ri Bhoi districts of Meghalaya, where diversity is higher.…”
Section: Discussionmentioning
confidence: 98%
“…While several studies have shown reduced genetic diversity in peripheral compared with central populations (Arnaud‐Haond et al., 2006; Durka, 1999; Eckert et al., 2008; Eckstein et al., 2006; Lammi et al., 1999), our results showed an alternative pattern where other interacting factors may override the presumed effects of the center–periphery hypothesis. Cneorum tricoccon populations located at range margins tended to show lower genetic diversity ( P , A , H O, H E ) and higher inbreeding ( F IS ) than central populations, although differences were not significant.…”
Section: Discussionmentioning
confidence: 99%
“…It is often assumed that peripheral populations are small, isolated, and occur in ecologically marginal habitats where selection pressures are likely to be more intense (Brown, Stevens, & Kaufman, 1996; Eckert et al., 2008; Lawton, 1993; Lesica & Allendorf, 1995; Pulliam, 2000). Such populations can have low genetic diversity as a consequence of high inbreeding, genetic drift, and directional selection and may also show strong genetic structure due to reduced gene flow (Arnaud‐Haond et al., 2006; Durka, 1999; Gapare & Aitken, 2005; Lammi et al., 1999; Schaal & Leverich, 1996). However, it is not known to what extent the effects of periphery are confounded by those of population size.…”
Section: Introductionmentioning
confidence: 99%
“…The samples were obtained from one region, which could be considered to be at the northern edge of the range of this butterfly in Central Europe. Many studies have indicated a lower genetic diversity, in terms of microsatellite polymorphism, in peripheral populations relative to core populations (Rossiter et al, 2000;Bouzat & Johnson, 2004;Faugeron et al, 2004;Arnaud-Haond et al, 2006). If this is the case then more intensive sampling over a wider range of the species distribution should result in more alleles being identified in the loci analysed.…”
Section: Discussionmentioning
confidence: 99%